Indigenous Eco-feminism in Kalitanjung Kejawen People as an Alternative to Preserve the Nature - Putra, Aqiel Sifa’ Abdallah; Lutfi, Mutohar (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2023)
Indigenous religions recognize the importance of natural elements in their lives, embodying traditional ecofeminism. Consequently, they bear the responsibility for properly maintaining and safeguarding nature to prevent damage or exploitation. Moreover, Indigenous Peoples, united in their efforts to protect nature, are inseparable from the crucial role and encouragement provided by remarkable indigenous women, such as those within the Kejawen Kalitanjung Banyumas Indigenous People. The concept of Indigenous Eco-feminism significantly influences the development of the Kejawen community. To support this research, qualitative methods with an emphasis on field research are employed. The primary method of direct data collection involves interviews with sources from traditional Kejawen Kalitanjung community leaders, complemented by documentation. Thus, the indigenous women of the Kejawen Kalitanjung community play diverse roles, actively participating and leading in the protection of their nature as a cohesive whole.